TITLE: INTERGENERATIONAL DIALOGUE ON THE IMPORTANCE OF RECONCILIATION, HEALING AND AWARENESS IN SOUTH SUDAN. - Alierr, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
the dialogue across generations can be used as a way to decrease the level of violence by using the knowledge and experience of previous generations to create awareness and to promote long term solutions for the risks faced by the community in South Sudan. In other word Intergenerational dialogues are interactive participatory forums that bring together older and younger generations and are intended to create shared knowledge and meaning and a collective experience. Intergenerational equity in economic, psychological, and sociological contexts, is the concept or idea of fairness or justice between generations. The concept can be applied to fairness in dynamics between children, youth, adults and seniors, in terms of treatment and interactions. Reconciliation is about strengthening relationships between the warring parties or parties caught up in conflict in other word this is a step whereby the parties caught up in conflict open a new page of peaceful coexistence for the benefit of all entirely citizen living in a given state E-g South Sudan. Reconciliation is an ongoing journey that reminds us that while generations of South Sudan   fought but they still come together for the development and prosperity for our county. Our vision of reconciliation is based and measured on five dimensions: historical acceptance; race relations; equality and equity; institutional integrity and unity. The dimensions do not exist in isolation, but are interrelated. Reconciliation cannot be seen as a single issue or agenda; the contemporary definition of reconciliation must weave all of these threads together. For example, greater historical acceptance of the wrongs done to One another that can lead to improved race relation.